Life without Lead : Contamination, Crisis, and Hope in Uruguay - Renfrew, Daniel, 1974- (Book collections on Project MUSE., 2019)
Drawing on political ecology and science studies perspectives, 'Life without Lead' examines the social, political, and environmental dimensions of a devastating lead-poisoning epidemic.